Original paperProstate-specific antigen bounce predicts for a favorable prognosis following brachytherapy: a meta-analysis - Bernstein, Michael B.; Ohri, Nitin; Hodge, James W.; Garg, Madhur; Bodner, William; Kalnicki, Shalom; Dicker, Adam P.; Guha, Chandan (Journal of Contemporary Brachytherapy, 2013)
Purpose: Controversy exists whether the prostate-specific antigen (PSA) bounce phenomenon following definitive radiation for prostate cancer has prognostic significance. Here, we perform a meta-analysis to determine the association between PSA bounce and biochemical control after brachytherapy alone. Material and methods: We reviewed Medline, EMBASE, and CENTRAL citations through February 2012. Studies that recorded biochemical failure rates in bouncers and non-bouncers were included. Hazard ratios describing the impact of bounce on biochemical failure were extracted directly from the studies or calculated from survival curves. Pooled estimates were obtained using the inverse variance method. A random effects model was used in cases of significant effect heterogeneity (p < 0.10 using Q test). Results: The final analysis included 3011 patients over 6 studies treated with brachytherapy. Meta-analysis revealed that patients experiencing PSA bounce after brachytherapy, conferred a decreased risk of biochemical failure (random effects model HR = 0.42, 95% CI: 0.30-0.59; p < 0.001). Conclusions : Our meta-analysis determined that PSA bounce predicts for improved biochemical control following brachytherapy. To our knowledge, this is the first study describing this effect.